Role of magnetic resonance imaging in bladder cancer: current status and emerging techniques - Green, David A.; Durand, Matthieu; Gumpeni, Naveen; Rink, Michael; Cha, Eugene K.; Karakiewicz, Pierre I.; Scherr, Douglas S.; Shariat, Shahrokh F. (BJU international, 2012)
What's known on the subject? and What does the study add? According to current treatment guidelines, magnetic resonance imaging (MRI) or computed tomography (CT) can be used to assist in staging bladder cancer patients being considered for radical surgery. In this article, we review the evidence supporting the use of MRI for bladder cancer staging. The ability of MRI to differentiate non‐muscle invasive from muscle‐invasive bladder cancer, to differentiate organ‐confined from non‐organ‐confined bladder cancer, and to identify lymph node metastases is described in detail. Additionally, the role of MRI as a biomarker of chemotherapeutic response in bladder cancer is reviewed and summarized. OBJECTIVES • To evaluate the current status of magnetic resonance imaging (MR) as a staging tool for bladder cancer. • To investigate the role of MR in assessing chemotherapeutic response in bladder cancer patients. PATIENTS AND METHODS • A Pubmed/MEDLINE search was conducted to identify original articles, review articles, and editorials regarding the use of MR in bladder cancer. RESULTS • Contrast‐enhanced MR and diffusion weighted MR (DW‐MRI) can likely distinguish between non‐muscle invasive bladder cancer and muscle invasive cancer with >80% accuracy. • Some advantages of DW‐MRI are the differentiation of benign versus malignant tissue involvement without the need for intravenous contrast, and the possibility of obtaining information on histologic grade and T stage. • Traditional MR sequence have low sensitivity for identifying small lymph node metastases but MR lymphography (MRL) using ultra‐small paramagnetic iron oxide (USPIO) may enhance their detectin. • There may be a role for DW‐MRI in the evaluation of chemotherapeutic response in bladder cancer patients. CONCLUSION • To date, sample sizes and study designs are insufficient to clearly establish the role of MR in bladder cancer management, and to this end, well designed prospective trials are needed.